2014
DOI: 10.1002/ccd.25374
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome in patients with ST segment elevation myocardial infarction and multivessel disease treated with culprit‐only, immediate, or staged multivessel percutaneous revascularization strategies: Insights from the REAL registry

Abstract: Our findings support the current guidelines recommendation to perform culprit-only PPCI in STEMI patients with MVD without hemodynamic compromise, followed by a staged PCI of noninfarct-related significant lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 33 publications
1
18
0
2
Order By: Relevance
“… PCI options for patients with STEMI and multivessel disease include: 1) culprit artery–only primary PCI, with PCI of nonculprit arteries only for spontaneous ischemia or intermediate‐ or high‐risk findings on predischarge noninvasive testing; 2) multivessel PCI at the time of primary PCI; or 3) culprit artery–only primary PCI followed by staged PCI of nonculprit arteries. Observational studies, randomized controlled trials (RCTs), and meta‐analyses comparing culprit artery–only PCI with multivessel PCI have reported conflicting results, likely because of differing inclusion criteria, study protocols, timing of multivessel PCI, statistical heterogeneity, and variable endpoints (Data Supplement).…”
Section: Culprit Artery–only Versus Multivessel Pcimentioning
confidence: 99%
“… PCI options for patients with STEMI and multivessel disease include: 1) culprit artery–only primary PCI, with PCI of nonculprit arteries only for spontaneous ischemia or intermediate‐ or high‐risk findings on predischarge noninvasive testing; 2) multivessel PCI at the time of primary PCI; or 3) culprit artery–only primary PCI followed by staged PCI of nonculprit arteries. Observational studies, randomized controlled trials (RCTs), and meta‐analyses comparing culprit artery–only PCI with multivessel PCI have reported conflicting results, likely because of differing inclusion criteria, study protocols, timing of multivessel PCI, statistical heterogeneity, and variable endpoints (Data Supplement).…”
Section: Culprit Artery–only Versus Multivessel Pcimentioning
confidence: 99%
“…We identified 18 studies that met criteria for review. Studies were included if they were: (1) either a RCT of any size, or an observational study containing more than 25 patients per treatment arm, (2) were published in a peer reviewed journal, and (3) reported mortality rates for patients undergoing either MVI or CVI‐only at the time of primary PCI.…”
Section: Methodsmentioning
confidence: 99%
“…6,19 Manari et al found that while there was a survival benefit in the long term for MV-PCI this was mitigated by the increased short-term mortality associated with that strategy, ultimately leading to support of current guidelines. 9 Additionally there are a number of other studies which support of the current guidelines including Kornowski and Toma. 20,4 The primary aim of this retrospective cohort study is to compare the occurrence of major adverse cardiac event (MACE) at follow-up from one geographic center for patients with acute STEMI and MVD by non-CL management strategies which were categorised as; medical management only, PCI, or CABG.…”
Section: Introductionmentioning
confidence: 96%
“…[5][6][7][8][9][10] Establishing the most effective treatment strategies in this clinical scenario is therefore important both because it constitutes a large proportion of STEMI presentations, and because of the high risk for poor prognosis.…”
Section: Introductionmentioning
confidence: 99%